2022
DOI: 10.1017/s0022029922000140
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the concentration of anti-Müllerian hormone and antral follicle count in pasture-managed Holstein cows in the high tropics

Abstract: We evaluated the relationship between plasma levels of anti-Müllerian hormone (AMH) and the number of antral follicles at the restart of the follicular wave in crossbred Holstein cows reared under extensive grazing systems over 2500 m above sea level. The study included 140 cows from 15 farms that were in average at the 75.3 ± 2.10 d post partum. Animals were synchronized according to the following regime: day 0 = intravaginal progesterone releasing device (IPD) + estradiol benzoate (EB); day 7: withdrawal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…The AFCs obtained align with previous findings in cows under similar grazing management (Ayala Guanga et al, 2022). However, Holstein cows in tropics, fed total mixed rations exhibited between 11% (Gobikrushanth et al, 2017) and 25% (Furukawa et al, 2020) more antral follicles.…”
Section: Resultssupporting
confidence: 90%
“…The AFCs obtained align with previous findings in cows under similar grazing management (Ayala Guanga et al, 2022). However, Holstein cows in tropics, fed total mixed rations exhibited between 11% (Gobikrushanth et al, 2017) and 25% (Furukawa et al, 2020) more antral follicles.…”
Section: Resultssupporting
confidence: 90%
“…For days open, it was found that GY × HO crosses reduced their ability to become pregnant when they were closer to pure breed Bos taurus . A possible explanation is the interaction between milk production and environmental adaptation (Guanga et al., 2022). A similar pattern is observed in BR × HO animals, whereas in the purebred Brahman, longer DO was also seen.…”
Section: Discussionmentioning
confidence: 99%
“…El número de FA menores a 4 mm valorado el d del inicio de la onda folicular (d 4) fue similar (P>0,05) en T1 (19,3 ± 0,75) y T2 (19,9 ± 0,62; FIG. 3A), lo cual permitió iniciar el estudio en condiciones similares en cuanto al RFA en los dos T. Los resultados del RFA observados fueron similares al reportado previamente en vacas Holstein mestizas alimentadas al pastoreo en el trópico alto ecuatoriano (17,26 ± 0,38 folículos [15], o el descrito para esta raza (18,5 ± 9,0 folículos) en zonas altas de países de cuatro estaciones [16].…”
Section: Recuento De Folículos Antrales El D Del Reinicio De La Onda ...unclassified